Financial Shenanigans : A Case Study in Malaysia - Ooi, Ki Wei (2013)
This study investigates the financial shenanigan cases which subject to the enforcement actions by the Malaysian Securities Commission between 2006 and 2011 for alleged financial misreporting. The scope of this study includes the attempts used, causes and consequences of the financial shenanigans and the post-financial shenanigans recovery plans devised to turnaround the companies. This study finds that the most common attempt used by the sample companies is overstating the revenue, follows by understating the expense accruals. Revenue and expenses are the major accounts that directly influence the net income of a company and therefore are the main targets for manipulation. As for the causes of financial shenanigans, evidence from this study shows that the sample companies which (i) intend to go for initial public offerings or transfer listing, (ii) are close to violation of debt covenants, (iii) have persistent equity overvaluation, and (iv) are audited by non-major audit firms are more likely to involve in financials shenanigans. This study also documents the consequences of financial shenanigans include downgraded debt securities, debt covenants violations and adverse stock market reaction upon the release of related news to the stock market. Last but not least, the investigation on the post-financial shenanigan recovery plans reveals that the common measures adopted by the sample companies are (i) equity reduction, (ii) debts settlements which are attached with rights of conversion into equity, and (iii) divestment of assets.